1992
DOI: 10.1016/0014-5793(92)80032-c
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and partial characterization of molecular forms of ceruloplasmin from human bile

Abstract: Highly purified ceruloplasmin (CP) was isolated from human bile using affinity chromatography. Billiary CP is represented by two molecular species. One of those is identical to oxidase CP from normal human serum while the other is analogous to oxidase‐lacking CP specific for the serum of the carriers of Wilson's mutation with respect to immunological specificity, electrophoretical mobility and molecular mass of the large fragments from spontaneous proteolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…It is also reported that normal human bile contains two molecular forms of ceruloplasmin. One is identical to the serum ceruloplasmin, and the other is similar to the ceruloplasmin without oxidase activity detected in patients with Wilson's disease (35).…”
Section: Biliur! Copper ~~C R C T I O T~supporting
confidence: 55%
“…It is also reported that normal human bile contains two molecular forms of ceruloplasmin. One is identical to the serum ceruloplasmin, and the other is similar to the ceruloplasmin without oxidase activity detected in patients with Wilson's disease (35).…”
Section: Biliur! Copper ~~C R C T I O T~supporting
confidence: 55%
“…In addition, both Cu-ATPases are possibly involved in efflux/influx of copper ions by the cell (Cox and Moore, 2002;Qian et al ., 1997), using for this purpose Cp secreted by cells (Gaitskhoki et al, 1990;Verbina et al, 1992). The choice of the listed brain regions, which can be easily identified anatomically, allowed us to compare the activity of CMS in neurosecretory cells (pituitary and hypothalamus), ependyma (choroid plexus), and different types of neurons (brain cortex, cerebellum, amygdala, and hippocampus).…”
Section: Methodsmentioning
confidence: 99%
“…This polypeptide was tentatively assigned by predominance and molecular mass to a subunit of α-2-macroglobulin (α2MG) 60 that can bind both copper and silver. 61…”
Section: Interaction Of Agnps With Cp and Other Serum Proteins In Vitromentioning
confidence: 99%